Geomorphological studies in terroirs characterization on the Abaucán valley, Catamarca province, Argentina - Moreiras, Stella Maris; Babelis, German Claudio; Bueno Grimalt, Luis Anibal; Schulz, Guillermo; Flores Cáceres, María Laura (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2024)
Poster